Ways to Improve Mental Activity of Students by Means of Integrated Lessons - Ortikova Zulfiya (Zien Journals, 2023)
This article describes ways to improve the mental activity of students through integrated lessons and factors of increasing the effectiveness of integrated lessons.
Keywords: Intellectual development; natural phenomena; their structure